2020
DOI: 10.2478/ceer-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Soil Sealing on Example of the Jedrzychow Residential Area in Zielona Gora, Poland

Abstract: The progressing urbanization leads to the growth of buildings within the cities and taking up new areas for investments. Uncontrolled urban sprawl entails a number of consequences resulting in the soil sealing of the areas which has been permeable so far. Cutting off deeper soil layers from gas exchange and access to water causes a reduction in biological activity and biodiversity. That is why EU considers soil sealing as one of the main problems of the 21st century.The paper attempts to analyze the progressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…the soils covered with impermeable and nearly-impermeable layers (pavement, asphalt, concrete, etc.) (Charzyński et al, 2011a(Charzyński et al, , 2011c(Charzyński et al, , 2017b(Charzyński et al, , 2018bKostecki et al, 2020). The impact of the soil sealing on microbiological and physicochemical properties of Ekranic Technosols was investigated in Toruń (Piotrowska-Długosz and Charzyński, 2015).…”
Section: Technogenic Soils In Urban Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…the soils covered with impermeable and nearly-impermeable layers (pavement, asphalt, concrete, etc.) (Charzyński et al, 2011a(Charzyński et al, , 2011c(Charzyński et al, , 2017b(Charzyński et al, , 2018bKostecki et al, 2020). The impact of the soil sealing on microbiological and physicochemical properties of Ekranic Technosols was investigated in Toruń (Piotrowska-Długosz and Charzyński, 2015).…”
Section: Technogenic Soils In Urban Areasmentioning
confidence: 99%
“…It was found that the sealing has influenced the soil properties and Ekranic Technosols are less exposed to the accumulation of pollutants. Very important issue in the context of soil sealing are the water problems commonly noted in the cities (Kostecki et al, 2020).…”
Section: Technogenic Soils In Urban Areasmentioning
confidence: 99%
“…Ekranosols (ekranosole) have technogenic hard layer (which is not a part of building or other construction) at the soil surface or at the depth of ≤5 cm. These are soils covered with a continuous and impermeable layer of asphalt, concrete, pavement, granite/marble plates, etc., common in the urbanized (squares, streets, cemeteries) and transportation areas (highways, airports, parking sites) (Charzyński et al, 2011b;Kostecki et al, 2020). The soil profile is isolated (sealed) from the top, thus the water, gases, nutrients and xenobiotics may cycle laterally only (Charzyński et al, 2011a;Mendyk and Charzyński, 2016).…”
Section: Classification Of Technogenic Soilsmentioning
confidence: 99%